PENGARUH KEWAJIBAN MORAL, PEMERIKSAAN PAJAK, DAN KONDISI KEUANGAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN UNTUK USAHA HOTEL YANG TERDAFTAR DI DINAS PENDAPATAN DAERAH KOTA PEKANBARU - Aryandini, Saumi; Savitri, Enni; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine empirically the effect caused by the variable moral obligation, tax audit, and financial condition with tax compliance on corporate taxpayers for hotel businessis registered in DISPENDA of Pekanbaru city. The sample used in this study taxpayer for the hotel business and is represented by the General Manager , Tax Officer and Owner Hotel . Collecting data this study used a questionnaire survey . The questionnaire distributed to 45 Hotel , about three questionnaires are not returned , and 42 ( 93 % ) returned the questionnaire filled out completely and can be processed . Data analysis methods used for testing the hypothesis is multiple regression analysis with SPSS ( Statistical Product and Service Solution ) version 21, with the level of significance 0,05 or 5 %.The results showed that moral obligations , tax audits , and financial condition of an effect on tax compliance on corporate taxpayers for the hotel business .Keywords: Moral obligation, Tax Audit, Financial Condition, and Tax Compliance